Semi-numerical simulation for the thermal performance of unsteady squeezing non-Newtonian MHD couple stress ternary hybrid nanofluid flow between parallel surfaces - Rehman, Ali; Saad, Abdullah Aziz; İnç, Mustafa; Abas, Siti Sabariah Binti; Jawo, Edrisa; Sudarmozhi, K. (Elsevier B.V., 2026)
A base fluid containing a three-component mixture of distinct nanoparticles called a ternary hybrid nanofluid (THNF). In single- or binary-hybrid nanofluids (HNF), these ternary systems exhibit synergistic thermal effects that enhance heat transfer more efficiently. The purpose of this research is to present a semi-numerical simulation and model for analysing the thermal performance of unsteady squeezing flow of a non-Newtonian magneto-hydrodynamic couple-stress THNF confined between 2 parallel surfaces, with the influence of viscous dissipation and heat generation. The THNF, synthesised by dispersing MWCNT,SWCNT,Agin a non-Newtonian base fluid, was investigated to investigate its superior energy transfer capabilities under complex flow regimes. The key nonlinear PDEs, accounting for squeezing motion, coupling stress effects, magnetic field (MF) interaction, and nanoparticle suspension, are converted into dimensionless nonlinear ODEs via suitable similarity transformations. A semi-numerical approach, the Homotopy analysis method (HAM), combining analytical and numerical schemes, is employed to achieve high-accuracy solutions for velocity and temperature fields. The influence of important parameters, such as the unsteady parameter, the couple stress parameter, the magnetic parameter, the nanoparticle volume fraction, the heat generation parameter, the rotation parameter, and the Eckert number, on the velocity and temperature profiles is observed. The results show that adding ternary hybrid nanoparticles greatly increases thermal conductivity, while the coupling stress and MHD parameters control energy dissipation and flow resistance. For engineering applications such as lubrication systems, extrusion processes, microfluidics, and biomedical devices, the analysis shows that squeezing dynamics and unsteady effects significantly influence energy transfer improvements. © 2025 The Author(s)
Keywords: Couple stress; Homotopy analysis method; MHD; MWCNT,SWCNT,Ag; ternary hybrid nanofluid